The implementation of monetary and fiscal rules in the EMU: a welfare-based analysis - Amedeo Argentiero (FIW - Research Centre International Economics, 2009)
This paper implements a methodology to evaluate the desiderability of monetary and fiscal rules within the context of the EMU using a DSGE model within a New Keynesian framework with sticky prices. The approach adopted is a welfare-based criterion that measures the welfare losses associated with these rules through a welfare loss function. Monetary policy follows a standard Taylor rule augmented by a stochastic component, driven by a union-wide monetary shock, whereas fiscal policy is made up of a countercyclical and debt-stabilizing public expenditure and of distortionary taxation on labor, dividends and interests on public bonds. We find that: 1) in the presence of our monetary rule alone, domestic inflation variance falls more than in the only presence of fiscal rules, whereas output gap smoothing is stronger in the only presence of fiscal rules; 2) the combination of our monetary rule and fiscal rules reduces welfare losses more than the same rules singly considered.
Keywords: E63; F41; E32; 330; Fiscal Rules; Monetary Rule; Feedback-on-Debt; Welfare Losses